An Efficient and Robust Data Compression Algorithm in Wireless Sensor Networks - Liang, Yao; Li, Yimei (IEEE communications letters, 2014)
Data compression is a useful technique in the deployments of resource-constrained wireless sensor networks (WSNs) for energy conservation. In this letter, we present a new lossless data compression algorithm in WSNs. Compared to existing WSN data compression algorithms, our proposed algorithm is not only efficient but also highly robust for diverse WSN data sets with very different characteristics. Using various real-world WSN data sets, we show that the proposed algorithm significantly outperforms existing popular lossless compression algorithms for WSNs such as LEC and S-LZW. The robustness of our algorithm has been demonstrated, and the insight is provided. The energy consumption of our devised algorithm is also analyzed.